2020
DOI: 10.1021/acssuschemeng.0c02789
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Absorption Performance of SiC/ZrC/SiZrOC Hybrid Nanofibers with Enhanced High-Temperature Oxidation Resistance

Abstract: In carbide ceramics, ZrC has a high melting point, high hardness, and excellent thermal conductivity and electrical conductivity. It can be used as a suitable additive phase for SiC nanomaterials to enhance its high-temperature resistance to oxidation and its microwave absorption property. In our work, heterogeneous SiC/ZrC/SiZrOC hybrid nanofibers with different ZrC contents are prepared using polycarbosilane and zirconium acetylacetonate as raw materials through electrospinning and hightemperature pyrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…The unique properties of CNFs such as high surface area, extraordinary length, low density, high porosity, and thermo-mechanical properties [40,41] qualify them for many different applications. This chapter covers a review of their applications related to tissue engineering [35,36,[42][43][44][45][46][47], sensors [32-34, 48, 49], water remediation [50][51][52][53][54][55][56], batteries [57][58][59][60][61][62][63], catalyst supports/catalysts [64][65][66][67][68][69][70][71], electromagnetic interference (EMI) shielding [72][73][74][75][76][77][78][79], and thermal insulation materials [26,[79][80][81][82], etc. A list of the recent studies about ceramic nanofibers by electrospinning method is presented in Table…”
Section: Applications Of Ceramic Nanofibersmentioning
confidence: 99%
See 2 more Smart Citations
“…The unique properties of CNFs such as high surface area, extraordinary length, low density, high porosity, and thermo-mechanical properties [40,41] qualify them for many different applications. This chapter covers a review of their applications related to tissue engineering [35,36,[42][43][44][45][46][47], sensors [32-34, 48, 49], water remediation [50][51][52][53][54][55][56], batteries [57][58][59][60][61][62][63], catalyst supports/catalysts [64][65][66][67][68][69][70][71], electromagnetic interference (EMI) shielding [72][73][74][75][76][77][78][79], and thermal insulation materials [26,[79][80][81][82], etc. A list of the recent studies about ceramic nanofibers by electrospinning method is presented in Table…”
Section: Applications Of Ceramic Nanofibersmentioning
confidence: 99%
“…The superior EMI shielding properties (high reflection loss together with wider EAB) imparted the composite nanofibers the potential to be used as reinforcements in polymer and ceramic matrix composites with EMI shielding properties [76]. Huo et al [72] prepared heterogeneous SiC/ZrC/SiZrOC hybrid nanofibers with different ZrC contents and analyzed them in terms of electrical conductivity, average diameter, and microwave-absorbing capability. When the ZrC concentration increased from 0 to 10 wt.%, decrease in average nanofiber diameter from 800 nm to 200 nm and increase in electrical conductivity from 0.3448 to 2.5676 S cm −1 were observed.…”
Section: Emi Shielding Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these composites, carbon fiber/phenolic (C/Ph) composites are widely utilized for the purpose of ablative thermal protection attributed to their high specific strength and ablative nature. The ablation characteristics of the C/Ph composites are strongly dependent on the type of matrix and the additives incorporated into them 2 . Effective char formation during pyrolysis process and low flammability coupled with low thermal conductivity make the phenolic resin a popular candidate as a matrix material for ablative composites.…”
Section: Introductionmentioning
confidence: 99%
“…Since microwaves were used for heating first in the last century, they has been widely used in various fields due to their high speed and effective heating effect. , Nowadays, the use of microwave treatment of chemical reactions has become a hot spot. , Microwaves heat a sample by converting electromagnetic energy into heat, , and the heating rate is uniform and fast. Since the process of microwave heating is energy conversion rather than heat transfer, heating can be started and stopped quickly as well as noncontact heating, so materials can be selectively heated. According to the experimental results, it was found that compared with conventional heat sources (such as steam and electric heaters), the use of microwave heating could achieve a higher product yield and better chemical reaction selectivity. In addition, using microwave heating could shorten the reaction time and increase the reaction rate.…”
Section: Introductionmentioning
confidence: 99%